Brand Ambassadors' Influence on Brand Image and Consumer Purchasing Decisions - Silvia Betrice Situmorang; Haris Herdiansyah (President University, 2022)
E-commerce has recently grown in popularity, particularly in Indonesia. Indonesia is the Southeast Asian country with the highest number of e-commerce visitors. Shopee and Tokopedia are currently the two largest e-commerce platforms in Indonesia. Shopee is a Singaporean company, and Tokopedia is an Indonesian company. To expand their market, both are currently using a brand ambassador, Shopee with Didi Kempot and Tokopedia with BTS. As a result, the researchers conducted this study to determine the influence of those brand ambassadors on brand image and consumer purchasing decisions, and they compared Shopee and Tokopedia to determine which one influenced them the most. This study included 222 respondents drawn from a population of young Indonesian college students using convenience sampling. To test the hypothesis, a simple linear regression analysis was used. This study discovered that Brand Ambassador Didi Kempot had an influence on Brand Image (sig. 2-tailed = 0.000 with R2 = 0.124) and Shopee Consumer Buying Decision (sig. 2-tailed = 0.000 with R2 = 0.062) and Brand Ambassador BTS had an influence on Brand Image (sig. 2-tailed = 0.000 with R2 = 0.243) and Tokopedia Consumer Buying Decision (sig. 2-tailed = 0.000 with R2 = 0.059). Furthermore, all independent variables had a positive influence on all dependent variables. The source of R2 demonstrated that all dependent variables were positive.